Integrating External and Internal Load for Monitoring Fitness and Fatigue Status in Standard Microcycles in Elite Rink Hockey - Fernández, Daniel; Moya, David; Cadefau, Joan A.; Carmona, Gerard (Frontiers in Physiology, 2021)
The aims of this study were threefold: firstly, to determine, describe and present an integrative approach to external and internal load dynamics for monitoring fitness and fatigue status of specific in-court rink hockey training sessions in a typical microcycle; secondly, to assess the differences between training sessions and matches; the third and final aim was to verify the association between external and internal load metrics. The external load, using a local positioning system, and internal load, using the rate of perceived exertion, were measured during 23 in-season microcycles for 9 top-level players. Training load data were analysed with regard to the number of days before or after a match (match day [MD] minus or plus). In relation to the first aim, internal and external load metrics merged into a single integrated system using pooled data z-scores provided an invisible monitoring tool that places the players in the fitness-fatigue continuum throughout the different microcycle sessions. In this regard, MD-4 and MD-1 sessions tend to place, with a low dispersion, the players in a “low external and internal load” zone, guaranteeing a recovery process. On the contrary, in MD-3 and MD-2 sessions, as well as in MD, in which higher loads were recorded, most of the players were within a “high external and internal load” zone with a tendency towards dispersion towards the fitness or fatigue zones. Finally, and with regard to the second and third aims, an inverted “U-shape” load dynamic related to the specific goals of each training session was the main finding in terms of comparison between MD; a load peak between MD-3 and MD-2 and a significant decrease in all the load variables in MD-1 was found; and high-to-low correlations were found between external and internal load metrics. This study presents an integrative approach to the external and internal load of players for monitoring fitness and fatigue status during a typical microcycle in rink hockey that might provide team sport staff members with a deeper understanding of load distribution in the microcycle in relation to the match.